(untitled) (Khairulummah, 2024)
The impact of Sufism on Islamic culture is profound, especially in areas like literature, poetry, and music. Sufism, with its mystical approach, deeply influenced the development of Arabic and Persian literature. Its emphasis on spiritual experience and divine love led to the creation of some of the most notable works in classical Islamic literature. For instance, poets like Ibn Arabi, Ibn al-Farid, and Abdul Ghani al-Nabulsi infused their verses with themes of divine unity, inner transformation, and the pursuit of closeness to God, which became central elements of Sufi poetry​ In terms of music, Sufism contributed significantly to the development of both the theory and practice of Islamic music. Sufis saw music, particularly mystical chants and instrumental music, as a way to purify the soul and elevate the spirit. The famous Sufi whirling dance (or dervish) and the use of instruments like the ney (flute) are just a few examples of how Sufis utilized music to transcend worldly concerns and experience divine presence​ Additionally, Sufism’s influence extended to architectural practices. While initially rejecting figurative sculpture, Sufis contributed to the creation of grand, symbolic structures, such as the domes and tombs of saints, which served as spiritual centers. These structures, adorned with intricate designs, became places for contemplation and remembrance, merging spiritual significance with artistic expression​.